Hydrometallurgical processing of complex sulphide ores Cashew for obtaining nickel and its salts - Lovera, Daniel (2013)
Peru maintains a leading position in the world mining in connection to production and extraction of metals like copper, zinc, silver, gold among others. Geological exploration and prospecting already carried out, show us a promissory future for the above mentioned minerals and other interesting findings like nickel in millerite ore which was proved in some ore deposits of the Marañón geological complex. This occurrence allowed us to carry out metallurgical investigation, specifically hydrometallurgical processing for the Peruvian sulphide ore aimed to the development of profitable mining operations for both private sector and the Peruvian state. We showed the metallurgical test results carried out at the metallurgical engineering school related to obtaining metallic nickel plates and its by products like cement and sulphate crystals.